Proceeding of Family of Generations is the Basis of Overcoming of Modern Family Relations Crisis - Володимир Kostiv (Pedagogical Discourse, 2012)
The article deals with the problem of proceeding of family culture of generations under the condicions of intensifying of modern crisis in family. Structural components of this integral property, the ways of forming of family culture of personality at the current period of time are outlined.